S-50-2: ULTRAFAST LC-MS ANALYSIS FOR THE CHEMICAL ADHERENCE TESTING: SUB MINUTE RUN TIMES FOR A PANEL OF NINE CARDIOMETABOLIC MEDICATIONS. (January 2023) - Lane, Dan; Ng, Leong; Jones, Donald JL; Gupta, Pankaj
Abstract : Objective: Non-adherence in hypertension can be as high as 30–45%. Chemical adherence testing (CAT) is the preferred method to assess non-adherence in European guidelines. New randomised controlled trials (RCTs), like the RADIANCE-HTN TRIO, have also started to implement CAT into their study framework to diagnoses non-adherence. Using high performance liquid chromatography (HPLC) in tandem mass spectrometry (MS/MS), existing quantitative urine CATs take > 40 minutes. These provide a yes/no answer. Recent guidance has suggested run-time be an area of development, along with the research of quantitative assays in plasma. Translated from the field of therapeutic drug monitoring, UltraFast (<1 minute) run times were explored using ultra performance short (UP)-LC columns with MS/MS for the detection and quantitation of nine cardiometabolic medications in plasma for use in CAT. UltraFast methods could increase clinical and research capacity while reducing cost. Design: An UltraFast quantitative CAT using UPLC-MS/MS was developed and optimised for the parallel detection of nine cardiometabolic medications in plasma. These medications were amlodipine, atenolol, atorvastatin, bisoprolol, edoxaban, enalapril, propranolol, ramipril, and saxagliptin. Methods: A mixed internal standard (IS; 10 ng/mL) was added to 100 μL of sample before the addition of 100 μL of water. The entire solution was added to pre-conditioned Oasis PRiME hydrophilic lipid balance (HLB) 96-well μElution solid phase extraction (SPE) plates. The loaded wells were washed (200 μL 5% methanol) and eluted (50 μL methanol/ acetonitrile) prior to UPLC-MS/MS analysis on a Waters Xevo TQ-XS triple quadrupole system. Sub 45 s run times were achieved using a Raptor Biphenyl Guard column cartridge (5 x 2.1 mm, 2.7 μm) as the UPLC column, used in reverse phase, and pumped at a 1.4 mL/min flow rate. Five replicate calibration curves were extracted over the range 0.01–500 ng/mL to assess model fits and detection limits. Results: All medications in plasma had lower limits of detection (LOD) between 0.01 ng/mL (atorvastatin) and 20 ng/mL (amlodipine). Optimum calibration curves were obtained. These were a mixture of quadratic and linear models. R2 ranged from 0.837 (enalapril) to 0.971 (atorvastatin). Clear chromatographic separation was achieved with the first eluted peak was atenolol, detected at 3 s. The last eluted peak was edoxaban at 22 s. Quantitation was possible over the range 0.01–500 ng/mL. Conclusion: A <45 second UPLC-MS/MS run time was achieved for a panel of nine cardiometabolic medications. LODs were well within the therapeutic range of interest, and quantitation was made possible over 0.01–500 ng/mL, the therapeutic range of interest. This method could be applied in clinical laboratories for same day adherence testing, or to large RCTs for their timely processing.